Un estudio de la dinámica del péndulo no lineal - Segovia-Chaves, Francis Armando; Dussán-Penagos, Anyery (Revista Científica, 2016)
We study the dynamics of nonlinear pendulum, which consists of a particle of mass m attached to the end of a light inextensible string of length l. Therefore we plot the variation of pendulum potential energy function of angle , as the corresponding phase diagram. The conditions imposed determine the behavior of the pendulum so that there is an oscillating movement and rotation, dependent on the value the maximum energy and potential energy is determined. As a case study the oscillator movement, analytically solve the differential equation of second order with reference Beléndez et al. paper, we get results when the system initially presents a nonzero angular velocity, The solutions obtained for the angular displacement versus time is in terms of the Jacobi elliptic functions sn (u, m ), we plot the angular displacement when the initial angular velocity is equal and non-zero . The results agree with those reported in Beléndez et al. The problem can be used to introduce concepts of elliptic integrals and motivate students to using computer software to analyze the solutions obtained.